THE COMPARISON BETWEEN MALE AND FEMALE STUDENTS’ SPEAKING ABILITY - Silpia Rahayu (STKIP Siliwangi, 2016)
The purpose of this research is to investigate the male and female students‟ speakingability. Particularly, this reserach has several aims: to know the male and femalestudents‟ speaking ability at SMAN 1 Bantarujeg, and to know the differencesbetween them. This research is presented in qualitative approach and comparativemethod to identify the male and the female students‟ speaking ability . In collectingthe data, the researcher did some steps. Those were observation and recorded spokentest. Then, the data was analyzed based on four indicators including pronunciation,grammar, vocabulary, and fluency. The researcher got the result, the average score ofmale is 13.5 and female is 14.8. Thefirst indicator is pronunciation, the male students‟score (35) is higher than the female students‟ score (34). The second is grammar, themale students‟score (31) is lower than the female students‟ score (38). The thirdisvocabulary, the male students‟ score (33) is lower than the female students‟score(41). The last is fluency, the male students‟ score (36) is higher than thefemalestudents‟ score (35). Based on the analysis, it can be concluded that there was asignificantdifference between the male and the female students‟ speaking ability. Keywords: speaking ability, teaching.